ANALISIS PROBABILISTIC FRACTURE MECHANICS PADA EVALUASI KEANDALAN BEJANA TEKAN REAKTOR SECARA 3-D - Hartini, Entin; Himawan, Roziq; Susmikanti, Mike (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Material integrity analysis is required for the reactor pressure vessel (RPV). The component is the pressure boundary that serves to contain radioactive materials. The presence of cracks on the walls can affect the integrity of the RPV. The objective of this study is to analyze fracture mechanics using probabilistic models for the evaluation of RPV reliability. Probabilistic models are used as an analysis approach for random character of input quantities such as the mechanical properties of materials and the physical environment. The random character of input quantities was obtained by sampling technique base on probability density function. The material used in this study was ferritic steel (SA 533). Fracture mechanics analysis was performed by Finite Element Method (FEM) with MSC MARC software. The outputs of MSC MARC, which is of J integral values, were converted into stress intensity factor (SIF) for evaluating the reliability of RPV in 3D model. It is found that the calculation resulted from the SIF by probabilistic method reaches a limit value of fracture toughness earlier than the SIF by deterministic method. The SIF generated by probabilistic method is 95,8 MPa m0.5, while the SIF generated by deterministic method is 91,8 MPa m0.5, where lower ratio value of (a/c) will produce greater value of SIF.